2017
DOI: 10.1097/icb.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Novel Retinal Complications After Endoscopic Sinus Surgery

Abstract: Macular edema, nonperfusion and ischemia, choroidal nonperfusion (Amalric sign), and atrophy can be iatrogenic sequelae of endoscopic ethmoid sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This indicated that patients with congenital MRP often required strabismus surgery to correct their exotropia as performed by an ophthalmologist, whereas patients with MRP resulting from midbrain infarction are usually managed with drug therapy as administered by neurologists. Endoscopic sinus surgery and trauma (81.25%) were the most common causes of the lesions in our study, consistent with that of previously described 5‐14 . Extraocular muscle injury, especially of the medial rectus, is a rare complication of endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This indicated that patients with congenital MRP often required strabismus surgery to correct their exotropia as performed by an ophthalmologist, whereas patients with MRP resulting from midbrain infarction are usually managed with drug therapy as administered by neurologists. Endoscopic sinus surgery and trauma (81.25%) were the most common causes of the lesions in our study, consistent with that of previously described 5‐14 . Extraocular muscle injury, especially of the medial rectus, is a rare complication of endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 91%
“…The extremely rare incidence of isolated MRP has severely limited the availability of information on the aetiology, clinical findings, imaging features and therapeutic outcomes of this condition. Based on previous studies involving 59 cases, the most common causes for MRP included complications after endoscopic sinus surgery as observed in 38 (64.40%) patients, followed by trauma in 11 (18.64%), midbrain infarction in eight (13.56%), complications after strabismus surgery in one (1.70%) and medial rectus muscle disinsertion by scleral buckle in one (1.70%) patient 5‐14 . To our knowledge, it is the first time to review isolated MRP, not as a single case presentation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations